2017
DOI: 10.1038/nm.4433
|View full text |Cite
|
Sign up to set email alerts
|

Selective neuronal lapses precede human cognitive lapses following sleep deprivation

Abstract: Sleep deprivation (SD) is a major source of morbidity with widespread health effects including increased risks of hypertension, diabetes, obesity, heart attack, and stroke1. Moreover, SD brings about vehicle accidents and medical errors2–4, and is therefore an urgent topic of investigation. During SD, homeostatic and circadian processes interact to build up sleep pressure5 that results in slow behavioral performance (cognitive lapses) typically attributed to attentional thalamic and fronto-parietal circuits6–1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
163
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 165 publications
(177 citation statements)
references
References 47 publications
13
163
1
Order By: Relevance
“…By analyzing small-amplitude, local slow waves in the occipital cortex separately from large amplitude slow waves, we showed that 8 h of blindfolding in human volunteers who listened to audiobooks (vs. movie watching, as control condition) led to a reduction in small, local slow waves in the occipital cortex during subsequent NREM-sleep. Moreover, visual deprivation also led to a decrease in occipital theta activity during wakefulness -another index previously suggested to reflect local homeostatic variations in sleep need (Bernardi et al, 2015;Hung et al, 2013;Nir et al, 2017). Importantly, standard analyses of SWA or of slow wave parameters (density, amplitude) in the present study did not show any significant changes.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…By analyzing small-amplitude, local slow waves in the occipital cortex separately from large amplitude slow waves, we showed that 8 h of blindfolding in human volunteers who listened to audiobooks (vs. movie watching, as control condition) led to a reduction in small, local slow waves in the occipital cortex during subsequent NREM-sleep. Moreover, visual deprivation also led to a decrease in occipital theta activity during wakefulness -another index previously suggested to reflect local homeostatic variations in sleep need (Bernardi et al, 2015;Hung et al, 2013;Nir et al, 2017). Importantly, standard analyses of SWA or of slow wave parameters (density, amplitude) in the present study did not show any significant changes.…”
Section: Discussioncontrasting
confidence: 43%
“…Wake EEG Recordings. Previous work showed that prolonged practice with particular tasks may lead to a local, regionally-specific increase in low-frequency activity during wakefulness in the theta range (5-9 Hz) (Hung et al, 2013), which may reflect experiencedependent changes in sleep need similar to local SWA during NREM-sleep (Bernardi et al, 2015(Bernardi et al, , 2016Hung et al, 2013;Nir et al, 2017;Pigarev et al, 1997). Thus, we also investigated regional (occipital) changes in theta activity during wakefulness after short-term visual deprivation.…”
Section: Methodsmentioning
confidence: 95%
“…In parallel, a growing body of evidence, expanded the notion of local sleep partially redefining the classical definition of wake and sleep as separate, discrete states. A number of studies in both rodents and humans demonstrated the occurrence of local sleep-like graphoelements intruding behavioral wakefulness over circumscribed cortical regions (14)(15)(16)(17)(18). A number of factors may account for such occurrence and include a regional-specific sensitivity to the activating signals from the brainstem and hypothalamic afferents (53,54), the diverse influence of the homeostatic process (55) over different brain structures and/or variable degrees of synaptic strength differentially impinging on local circuits in a use-dependent manner (56).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, in spite of their common features and possible mechanistic determinants, the lateralized slow waves occurring after focal brain injury have never been explicitly connected to the electrophysiology of sleep slow waves. Such a putative connection is particularly interesting when considering that slow waves and neuronal OFFperiods can occur locally not only during sleep (13), but also during wakefulness (some brain regions can be silent while others are active (14)(15)(16)(17)) with important consequences on behavior, including motor impairments as shown in awake, sleep-deprived rats performing a pellet reaching task (15), as well as cognitive lapses in awake humans (18).…”
Section: Introductionmentioning
confidence: 99%
“…Spike sorting was performed using the wave_clus toolbox for Matlab as described previously (87,88): (i) extracellular microwire recordings were high-pass filtered above 300Hz, (ii) a 5 ´ SDapproximation ( {| | 0.6745 ⁄ }) threshold above the median noise level was computed, (iii) detected events were clustered using superparamagnetic clustering, and categorized as noise, single-or multi-unit clusters. Classification of single-and multi-unit clusters was based on the consistency of action potential waveforms, and by the presence of a refractory period for single units, i.e.…”
Section: Analysis Of Neuronal Spiking Activitymentioning
confidence: 99%